Role of saxagliptin as monotherapy or adjunct therapy in the treatment of type 2 diabetes - Morali D Sharma (Dove Medical Press, 2010)
Morali D SharmaBaylor College of Medicine, Houston, Texas, USAAbstract: Type 2 diabetes is associated with decreased incretin hormone response to an oral glucose load, and a progressive decline in postprandial glucagon-like peptide-1 (GLP-1) secretion. Incretin-based therapies offer a new option for treatment of type 2 diabetes. Saxagliptin, a potent, selective dipeptidyl peptidase-4 (DPP-4) inhibitor specifically designed for extended inhibition of the DPP-4 enzyme, causes increased endogenous GLP-1 concentration. In a phase 3 clinical trials program of 24 weeks duration, saxagliptin was studied in 6 multicenter, multinational, randomized, controlled studies and in combination with 3 of the most commonly administered oral antidiabetic drugs: metformin, glyburide and a thiozolidinedione (TZD). Saxagliptin provided significant reductions in hemoglobin HbA1c when given with metformin, glyburide, a TZD, or as monotherapy. Saxagliptin also reduced fasting plasma glucose and 2-hour post-prandial glucose in each of these studies, and was weight and lipid neutral. Saxagliptin was well tolerated and had a low risk of hypoglycemia when used as monotherapy.Keywords: saxagliptin, incretins, type 2 diabetes, DPP-4 inhibitors